INTRAPERSONAL INTELLIGENCE RELATIONSHIP WITH 4-6 YEARS MORAL BEHAVIOR IN RA ULUL AZMI, PEKANBARU CITY - Syukria Elfyana; Zulkifli N (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This study aims to determine the relationship between intrapersonal intelligence with moral behavior of children for ages 4-6 years at RA Ulul Azmi Pekanbaru City. The population in this study were children aged 4-6 years in RA Ulul Azmi Pekanbaru City, amounting to 40 people. Because the population population is small, the entire population is sampled, as many as 40 people. The method used in this research is quantitative correlation to see the relationship between intrapersonal intelligence with moral behavior. Data collection techniques used are observation. Data analysis techniques using product moment correlation techniques with SPSS for Windows ver 17. Based on the results of hypothesis testing there is a significant positive relationship between intrapersonal intelligence with moral behavior in children aged 4-6 years in RA Ulul Azmi Pekanbaru City. This is known from the correlation coefficient of rxy = 0.549 and a significance level of 0.000 <0.05. The level of relationship between intrapersonal intelligence with moral behavior is included in the medium category with the resulting determinant coefficient value of KD = r2 x 100% = 30.1%, meaning that intrapersonal intelligence gives an influence of 60.2% on moral behavior. Penelitian ini bertujuan untuk mengetahui hubungan antara kecerdasan intrapersonal dengan perilaku moral anak untuk usia 4-6 tahun Di RA Ulul Azmi Kota Pekanbaru. Adapun populasi dalam penelitian ini adalah anak usia 4-6 tahun Di RA Ulul Azmi Kota Pekanbaru yang berjumlah 40 orang. Karena julmah populasi kecil maka seluruh populasi dijadikan sampel yaitu sebanyak 40 orang. Metode yang digunakan dalam penelitian ini yaitu korelasi kuantitatif untuk melihat hubungan antara kercerdasan intrapersonal dengan perilaku moral .teknik pengumpulan data yang digunakan yaitu observasi. Teknik analisis data menggunakan teknik korelasi product moment dengan program SPSS for Windows ver 17. Berdasarkan hasil uji hipotesis terdapat hubungan positif yang signifikan antara kecerdasan intrapersonal dengan perilaku moral pada anak usia 4-6 tahun Di RA Ulul Azmi Kota Pekanbaru. Hal ini diketahui dari nilai koefisien korelasi sebesar rxy=0,549 dan taraf signifikansi 0,000 < 0,05. Tingkat hubungan antara kecerdasan intrapersonal dengan perilaku moral termasuk dalam kategori sedang dengan nilai koefisien determinan yang dihasilkan adalah sebesar KD = r2 x 100% = 30,1%, memiliki makna bahwa kecerdasan intrapersonal memberi pengaruh sebesar 60,2% terhadap perilaku moral.